PERANCANGAN MEDIA PROMOSI PRODUK UNGGULAN UKM KENDAL BERBASIS WEB DENGAN METODE R&D - Moh Muthohir (STEKOM PRESS, 2019)
Based on observations, UKM have limitations in terms of online marketing.This research aims to present a web design that is able to provide information that can be used to improve marketing or promotion of UKM products in Kendal City.the method used to develop the system is R&D (Research and Development).The results showed that this system is said to be feasible as an effective online promotion media based on the assessment of web expert validator with a value of 2.9 and a validator of UKM with a value of 3.4